Meat Quality Evaluation of Broiler Breast Fillets Affected by Aging Time and Marination - Perlo, F.; Bonato, P.; Fabre, R.; Teira, G.; Tisocco, O. (International Journal of Poultry Science, 2010)
Poultry meat production in Argentina has experienced an important increase. Poultry processors have incorporated different strategies to reduce processing time and improve quality of breast fillets. The aim of the study was to evaluate the effect of deboning time and marination on meat quality of broiler breast fillets produced in Argentina. Three hundred sixty commercial 48 d old male broilers were aged for 0, 2, 4, 6, 8 or 24 h before deboning. After deboning pH and color were determined. The right fillet of each breast was immediately quick-frozen and the left fillet was marinated by injection and then quick-frozen. All breast fillets were stored when frozen for 60 d and then thawed for pH, color, Warner-Bratzler shear force and thawing loss determinations. pH measured at deboning decreased during the first 4 h of aging in not marinated fillets. Measures taken after frozen storage showed no changes in pH with aging time. Lightness measured at deboning increased with aging time. Shear values in both marinated and not marinated fillets decreased as from 6 h of aging. Furthermore, marinated treatment reduced shear values in all aging time.